2023
DOI: 10.1038/s41420-023-01304-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous blockade of VEGF-B and IL-17A ameliorated diabetic kidney disease by reducing ectopic lipid deposition and alleviating inflammation response

Abstract: The pathogenesis of diabetic kidney disease (DKD) is complicated. Current clinical treatments fail to achieve satisfactory efficacy in the prevention of DKD progression, it urgently needs novel and effective treatment for DKD. In this study, we firstly demonstrated that renal lipid metabolism abnormality and inflammation significantly changed in DKD conditions by mining public transcriptomic data of DKD patient samples. KEGG analysis further exhibited the critical role of vascular endothelial growth factor B (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…A study demonstrated that, in the DKD mouse model, blocking IL-17a signaling utilizing neutralizing antibodies manifested a potentiated impact on reducing nephropathy and improved renal functioning by reducing lipid accumulation. Therefore, the concurrent impediment of IL-17a might represent a new and efficient management approach (Cao et al ., 2023)[ 7 ] (Guedes and Pecoits-Filho, 2022). [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated that, in the DKD mouse model, blocking IL-17a signaling utilizing neutralizing antibodies manifested a potentiated impact on reducing nephropathy and improved renal functioning by reducing lipid accumulation. Therefore, the concurrent impediment of IL-17a might represent a new and efficient management approach (Cao et al ., 2023)[ 7 ] (Guedes and Pecoits-Filho, 2022). [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Among these cytokines, interleukin (IL)-17a has been extensively studied for its involvement in autoimmune-mediated and inflammation-related disorders and may also contribute to renal inflammation damage (Li et al ., 2019). [ 6 ] Furthermore, other studies suggest that IL-17a is implicated in both acute and persistent nephropathy (Cao et al ., 2023)[ 7 ] (Chen et al ., 2022). [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mehlem et al [ 50 ] found that VEGFB signaling is involved in regulating pathological lipid accumulation in diabetes, obesity, and cardiovascular disease and mainly affects mitochondrial genes related to the regulation of fatty acid intake. Cao et al [ 51 ] showed that VEGFB/IL-17 inhibits the expression of fatty acid transporters to reduce the accumulation of renal lipids and inhibit renal oxidative stress and mitochondrial dysfunction, thus improving the inflammatory response. Shen et al [ 52 ] also found that VEGFB/IL-22 can not only regulate glucose and lipid metabolism but also reduce inflammation and ROS accumulation.…”
Section: Vegfb Participates In Regulating the "Second Hit" In Nafldmentioning
confidence: 99%
“…Ectopic lipid accumulation frequently occurs in tubulointerstitial fibrosis and the restoration of fatty acid metabolism protects against tubulointerstitial fibrosis [ 47 ]. In addition, ectopic lipid accumulation accelerates the proinflammatory response, which is also related to the development of tubulointerstitial fibrosis [ 48 ]. ACSL1 was down-regulated in obesity-associated nephropathy accompanied with increased lipid accumulation and triglyceride content [ 21 ].…”
Section: Discussionmentioning
confidence: 99%